The Trends of Remuneration for Work in the Context of Globalization of Economy - Gerikienė, Valerija; Marčinskas, Albinas (Ekonomika, 2002)
A system of remuneration for work includes monetary relations, such as salaries of employees, hourly wage, premiums, various benefits and privileges provided to employees by the employer. On the analysis of the data published by the Government of Republic of Lithuania Statistical Department, the following trends of remuneration for work in Lithuania were disclosed: on permanent increase of the average remuneration for work in the country. the increase of the real remuneration for work is inconsiderable and in some years a decrease takes place; the number of employees working for the minimal remuneration that in Lithuania is much lower than in states of the European Union is increasing; other forms of remuneration for work are rarely used in addition to base remuneration. The trend of orientation of employers to saving funds at the expense of the remuneration for work to employees and formation of the image of a cheap manpower state with all corresponding consequences in sufficiently evident in Lithuania.